2023
DOI: 10.3390/molecules28062591
|View full text |Cite
|
Sign up to set email alerts
|

Milk Thistle Oil Extracted by Enzyme-Mediated Assisted Solvent Extraction Compared with n-Hexane and Cold-Pressed Extraction

Abstract: Silymarin and milk thistle oil have unique biological benefits; however, applying silymarin to milk thistle oil remains a challenge. In this research, the content of silymarin in milk thistle oil conditions using enzyme-mediated solvent extraction was investigated and optimized by response surface methodology. The optimal extraction conditions using enzyme-mediated solvent extraction were as follows: the enzyme-added content was 3.06 mg/mL, the enzymatic hydrolysis temperature was 55.09 °C, and the enzymatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Although the solvent was chosen according to previous research [10,11], the residual methanol may pose a health concern in the medical application of the extracts. In future research, there is an opportunity to enhance our processes by drawing on insights from successful studies related to milk thistle or silymarin [41,42], which have demonstrated effective optimization strategies. Additionally, we should note that our study did not examine the biological activity or toxicity of other ingredients; therefore, future studies should evaluate the antioxidant potential of these additional components.…”
Section: Discussionmentioning
confidence: 99%
“…Although the solvent was chosen according to previous research [10,11], the residual methanol may pose a health concern in the medical application of the extracts. In future research, there is an opportunity to enhance our processes by drawing on insights from successful studies related to milk thistle or silymarin [41,42], which have demonstrated effective optimization strategies. Additionally, we should note that our study did not examine the biological activity or toxicity of other ingredients; therefore, future studies should evaluate the antioxidant potential of these additional components.…”
Section: Discussionmentioning
confidence: 99%